Hypertonic saccharide solution delays pyroptosis in murine macrophages regardless of the membrane binding of gasdermin D N‐terminal. Issue 3 (10th December 2019) - Zheng, Jiashuo; Wang, Dingyu; Chen, Qianyue; Liu, Qiyao; Lin, Zhaoyu; Hu, Qiongyuan; Wu, Xiuwen; Gao, Xiang; Li, Qiurong; Ren, Jianan
Abstract: Pyroptosis is a type of programmed lytic cell death that could be activated by either the canonical or noncanonical inflammasome pathway. In this study, we aimed to examine the effect of hypertonic solution on noncanonical pyroptosis in macrophage. We found that although hypertonic solution had a general inhibitory effect on noncanonical pyroptosis, the underlying mechanism varied by the solute causing hypertonicity. Specifically, hypertonic NaCl or KCl solution inhibited the cleavage of gasdermin D, the pore‐forming protein in pyroptosis, whereas hypertonic saccharide solution did not affect the cleavage or membrane binding of gasdermin D. In this case, nevertheless, pyroptosis was still inhibited as evidenced by the preserved mitochondria activity and cell membrane permeability. Abstract : Noncanonical pyroptosis is mediated by gasdermin D (GSDMD) downstream of caspase‐11 activation by LPS. While hypertonic (∼500 mOsm) NaCl or KCl solution impedes this process by blocking GSDMD cleavage, hypertonic saccharide solution delays pyroptosis without affecting GSDMD pore formation.